Impact of Brand Loyalty on Customer Satisfaction (An Empirical Analysis of Clothing Brands) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose of the study: This study explored to prove whether this relationship really exists or not. So author examined the case of a clothing brand. Three different types of customer satisfaction were distinguished: (i) satisfaction with the clothes; (ii) satisfaction with the sales service and (iii) satisfaction with the after‐sales service. It was expected that all three types of satisfaction would be influenced by brand loyalty.Methodology: Three brans have been selected three famous brands of Pakistan (Ideas, Outfitters and J.). and researched on them from 2018-2019. We have mail and got 122 responses from the customers of these brands and we have physically filled some questionnaires from customers also and collected an integrated data of 151 responses. The three different types of customer satisfaction and the intention to buy the same brand of clothe again, as well as the intention to buy from the same dealer again were measured.Main Findings: The analyses of the results revealed that: customer satisfaction with the clothes is major determinants of brand loyalty. In this case Customer satisfaction is dependent and brand loyalty is independent because they have a causal relationship because when the brand will be loyal to its customers then the customers will be satisfied with the brand. Our brands are the most famous brands and are the market setters and compete with each other very well. So, we have selected these because they all are most accurate according to our research topic and there is no bias sampling in these sample. Furthermore, it was found that the strength of the relationship between different types of satisfaction and loyalty is the quality of clothes and the after services given by the brand.Application of this study: This study will contribute toward new clothing brands who they are new in their track and struggling for the customer satisfaction with loyalty. Furthermore, the results of this study also can help out to the brands that has been taken as sample to understand their market and to improve them.